PEMIMPIN YANG KREDIBLE DAN YANG - Allo, Yusuf Rombe M. (Fundamental Management Journal, 2019)
Leadership is a process to influence or to give examole by by the leaders to their followers ini order to achieve the goal of the group or the company organization. The natural way to lern leadership is to do it in the job and to be an apprentice for a lecture, practitioner etc. in this relation the leaders are expected to give their role as a lesson / instruction. Credible leaders are leaders with hagh integrity who use thei power etically and morally, fair and correct for their community. Only the credible leaders could be a leader of vision who could rely on their way towards the future together. Key Word : Credible leaders and leader of vision ae the process of influencing ethically and morally.